RelB is a potential molecular biomarker for immunotherapy in human pan-cancer - Wu, Jintao; Yu, Xinyu; Zhu, Hongyu; Chen, Peng; Liu, Tongyan; Yin, Rong; Qiang, Yan; Xu, Lin (Frontiers in Molecular Biosciences, 2023)
The nuclear factor kB (NF-kB) consists of a family of transcription factors emerged in many biological responses. NF-κB is well-known for modulating the immune activations and inflammation. Besides, NF-κB signaling had diverse and complicated roles in cancer with studies that NF-κB could both contribute to tumor promotion and suppression of oncogenesis relying on the cellular context. However, it remained to be illustrated that RelB expression, clinical features and the association with tumor-infiltration cells in human pan-cancer. In this study, we investigated the aberration expression and prognostic significance of RelB, and the correlation with clinicopathological characters and immune cells infiltration in various cancer. We used TCGA and GTEx databases to analyze the mRNA expression level in different cancer types. Kaplan-Meier analysis and Cox regression were used to explore the prognostic significance of RelB in human pan-cancer. Then we took advantage of the TCGA database to analyze the relationship between RelB expression and DNA methylation, the infiltration of immune cells, immune checkpoint genes, tumor burden (TMB), microsatellite instability (MSI), mismatch repair (MSS). Higher expression of RelB was significantly detected in human cancer tissues and a high level of RelB expression was significantly linked with a worse outcome in LGG, KIPAN, ACC, UVM, LUAD, THYM, GBM, LIHC and TGCT but associated with a favorable overall survival (OS) in SARC, SKCM and BRCA. According to the Human Protein Altas database, RelB was considered as an independent factor in breast cancer and renal cancer prognosis. GSEA results revealed that RelB was involved in many oncogenesis-related processes and immunity-related pathways. RelB was significantly correlated with DNA methylation in 13 types of cancer. Meanwhile, RelB expression was associated with TMB in 5 types of cancer and MSI in 8 types of cancer. In the final, we analyzed the relationship between RelB expression and immune-infiltration cells in human pan-cancer, which suggested RelB could be a promising therapeutic target for cancer immunotherapy. Our study further provided insights into a deeper understanding of RelB as a prognostic biomarker.